Mulheres artesãs : extrativismo da taboa (Typha spp.) em Pacatuba/SE - Carvalho, Andréa Freire de (2018)
The cattail (Typha spp.) is the protagonist of the life histories of women extractivist-artisans, because it guarantees their sustainability in daily life. In this perspective, the main objective of the thesis was to point out how cattail promotes the socioenvironmental sustainability of women who attribute meanings to their actions as a way of surviving, in the face of the adversities of their daily lives. It had as specific objectives: to contextualize the actions and processes of women in the extraction of the Cattail, in order to influence the construction of socioenvironmental sustainability; identify spaces (social, educational, cultural and political) in which women express their experiences in daily life; to describe the meanings attributed by the woman to the extraction of the cattail in relation to the sociability and the commercialization of the products re-signified to the raw material of Typha spp. To achieve the objectives, oral history was used interwoven with social phenomenology, which allowed us to recall events and facts that led the women extractivist-artisans of cattail - as well as extractive-artisans from Ouricuri straw, fishermen, lace makers, seamstresses, straw braids artisans, housekeepers, ministers, sisters, mothers and wives - to incorporate in their routine ways of resisting and sustaining the family in the place of daily life. In this case, the research locus was the municipality of Pacatuba, State of Sergipe, Brazil. We also used interviews-dialogues, semistructured questionnaires, participation in meetings and events, field journals, theoretical readings and photographs as methodological tools, which allowed us to systematize the thesis. We conclude that, for extractive-artisan women, sustainability is delineated in daily life through actions that aim to keep Typha spp. in constant production and growth. It is not something that is discussed, it is something that is done, and it was transmitted to them by previous generations and by processes of observation of the daily life, especially since the knowledge of the correct management is passed from artisan to artisan, during the harvest, as well as in meetings in associations, craft centers, group meetings and also in prayer spaces. Finally, the meaning that these extractivist-artisans attribute to the cattail is summed up in one word: everything. "[...] The Cattail to us is everything".________________________________________________________________________________________________________________________________